Mental healthcare services satisfaction and its associated factors among patients with mental disorders on follow-up in the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Melkam, Mamaru; Kassew, Tilahun (Frontiers in Psychiatry, 2023)
Background Patient mental healthcare services satisfaction is a crucial component in evaluating the effectiveness and efficiency of clinical service delivery. It can be explained as the client’s reaction to various aspects of the services they receive and their subjective assessment of the healthcare facilities and healthcare givers. Despite the importance of measuring mental healthcare services satisfaction, few studies have been conducted in Ethiopia. This study aimed to assess the prevalence of mental healthcare services satisfaction among patients with mental disorders who were on follow-up at the University of Gondar Specialized Hospital, Northwest Ethiopia. Method An institution-based cross-sectional study was conducted from June 1, 2022 to July 21, 2022. All the study participants were interviewed on the follow-up visit consecutively. The Mental Healthcare Services Satisfaction Scale tool was used to measure patient satisfaction, and the Oslo-3 Social Support Scale and other questionnaires, such as environmental factors and clinical factors, were also screened. The data were checked for completeness, entered and coded using Epi-data version 4.6, and exported to Stata version 14 software for analysis. Bivariable logistic and multivariable regression analyses were employed to identify the factors significantly associated with satisfaction. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to report the result at a p-value of <0.05. Results A total of 402 study participants were included in this study, with a response rate of 99.7%. The proportions of male and female participants who were satisfied with the mental healthcare services were 59.29 and 40.70%, respectively. The overall mental healthcare services satisfaction was 65.46% with a 95% CI of 59.90, 70.62. Not being admitted to psychiatry [AOR: 4.94; 95% CI (1.30, 8.76)], getting their drugs in the hospital [AOR: 1.34; 95% CI (3.58, 8.74)], and having strong social support [AOR: 6.40; 95% CI (2.64, 8.28)] were significantly associated with satisfaction. Conclusion The prevalence of mental healthcare services satisfaction is very low; therefore, more is expected to be done to enhance the satisfaction of the patients who access these services via psychiatry clinics. Enhancing the social support of clients, making drugs available in the hospital, and improving the service received by the admitted client are necessary to increase the healthcare service satisfaction of clients on the whole. The services delivered in psychiatry units must be improved to achieve good patient satisfaction, which might be helpful for the improvement of the disorders.